Development of an Interactive Tool Using Articulate Storyline Based on the Contextual Approach to Enhance Reading Skills for First-Year High School Students in Banda Aceh, Indonesia - Azwir, Azwir; Cut Nikmatul Ulya, Cut Nikmatul Ulya; Zulkhairi, Zulkhairi (EL-MAQALAH : Journal of Arabic Language Teaching and Linguistics, 2025)
This developmental study aims to design an interactive tool using Articulate Storyline based on a contextual approach to enhance the reading skills of seventh-grade students at MTsN 1 Banda Aceh. The researcher adopted an instructional development model consisting of five stages: analysis, design, development, implementation, and evaluation. The process began with field observation and problem diagnosis, followed by consultations with experts to obtain appropriate modifications and suggestions. The experts’ evaluation results indicated that the design quality reached 95.8%, while the quality of style and content was 90%, suggesting that the educational product is highly valid for use in teaching reading. Furthermore, a paired-sample t-test showed that the Sig. (2-tailed) value was 0.00, which is below the significance level of 0.05, indicating the effectiveness of the developed interactive tool in improving reading skills and leading to the rejection of the null hypothesis in favor of the alternative hypothesis. Students’ responses to the interactive tool were very positive, with a mean score of 32.52 (81.3%), classified as “very good,” demonstrating the tool’s contribution to enhancing students’ motivation toward learning reading skills and improving their comprehension of the texts.